2018
DOI: 10.1007/s10722-018-0635-4
|View full text |Cite
|
Sign up to set email alerts
|

Content and composition of essential oil and content of rosmarinic acid in lemon balm and balm genotypes (Melissa officinalis)

Abstract: Lemon balm (Melissa officinalis L.) is used since ancient times because of its sedative, spasmolytic and antiviral effects. Its therapeutic impact is due to the content of essential oil and rosmarinic acid. A set of 68 M. officinalis genotypes was evaluated for content and composition of essential oil and the content of rosmarinic acid. For all genotypes the level of ploidy was determined. The 68 genotypes were clone plants grown and evaluated for two years at Quedlinburg. For analysis of secondary metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…The principal constituents detected in the essential oil from M. officinalis by GC-MS were monoterpenes and sesquiterpenes (Table 1; GC-MS total ion chromatogram is shown in the Supplementary Figure S1), with composition data consistent with that previously reported for M. officinalis oil (Elliott et al, 2007), and with the citral chemotype reported for this species (Kittler et al, 2018a;2018b).…”
Section: Chemical Composition Of M Officinalis Oilsupporting
confidence: 87%
“…The principal constituents detected in the essential oil from M. officinalis by GC-MS were monoterpenes and sesquiterpenes (Table 1; GC-MS total ion chromatogram is shown in the Supplementary Figure S1), with composition data consistent with that previously reported for M. officinalis oil (Elliott et al, 2007), and with the citral chemotype reported for this species (Kittler et al, 2018a;2018b).…”
Section: Chemical Composition Of M Officinalis Oilsupporting
confidence: 87%
“…In plants of two genotypes, caryophyllene epoxide, germacrene-D and ß-caryophyllene had the highest sesquiterpene compounds, respectively, regardless of light treatments. As in the present study, in Jalal et al's study (2015), the main sesquiterpene of lemon balm was ß-caryophyllene epoxide (11%) and in the study of Kittler et al (2018) ß-caryophyllene, germacrene-D and ß-caryophyllene epoxide constituted the main sesquiterpene compounds of lemon balm genotypes. However, in the study conducted by Chung et al (2010), caryophyllene (0.8%) and farnesene (0.1%) were the most common sesquiterpene.…”
Section: Sesquiterpenes Content Under Various Light Treatments In Twosupporting
confidence: 74%
“…Kittler et al (2018) ß-caryophyllene, germacrene-D and ß-caryophyllene epoxide constituted the main sesquiterpene compounds of lemon balm genotypes. However, in the study conducted byChung et al (2010), caryophyllene (0.8%) and farnesene (0.1%) were the most common sesquiterpene.…”
mentioning
confidence: 98%
“…Different organic compounds present in lemon balm extract including protein, essential oils, avonoids, rosmarinic, caffeic and gallic acids and phenolic contents are responsible for bio-reduction of Ag + ions [19,21]. M. o cinalis as a valuable source of natural antioxidants has strong antimicrobial activity [22,23]. In the present study, silver nanoparticles (AgNPs) were synthesized using aqueous and methanolic extracts of Melissa o cinalis.…”
Section: Introductionmentioning
confidence: 99%